The Spectral Method for Solving Sine-Gordon Equation Using a New Orthogonal Polynomial. (2nd February 2012) - Soori, Zoleikha; Aminataei, Azim
Abstract : We have presented a numerical scheme for solving one-dimensional nonlinear sine-Gordon equation. We apply the spectral method with a basis of a new orthogonal polynomial which is orthogonal over the interval [ 0, 1 ] with weighting function one. The results show the accuracy and efficiency of the proposed method.